Evolution of peritoneal dialysis in France since 2018 and during the «COVID years. RDPLF data report - Christian Verger; Emmanuel Fabre (RDPLF, 2022)
Almost all (99%) of the patients treated by peritoneal dialysis in France are registered in the RDPLF database. Apart from any statistical analysis aimed at interpreting the figures, this work is a report of the raw data observed in the population of Stage V renal failure patients treated by peritoneal dialysis since the beginning of the Covid epidemic and in the two years preceding it. Since the beginning of the epidemic, these data seem to show a decrease in the incidence of peritoneal dialysis treatment and an increase in transfers to center-based hemodialysis. In addition, there has been a decrease in the number of registrations on the transplant waiting list and a decrease in the number of transplants. While the temporary decrease in transplantation activity may be explained by the disorganization caused by the epidemic in the hospitals, a decrease in the number of indications for home dialysis probably merits further reflection on its causes, especially since this result is in contrast with trends in other countries. This report is intended to encourage more precise studies on the value of home dialysis during the epidemic.